Antecedents to effective e-learning among selected secondary schools in Malaysia - Palanisamy, Subramaniam; Ahlan, Abdul Rahman; Atanda, Balogun Naeem (University of Ilorin, Ilorin, Kwara State, Nigeria), 2017)
As the e-learning technology continued to evolve, targeting antecedents to it effectiveness in Malaysia can be a prerequisite to increasing the success rate of this initiative. Students use e-learning for their schooling activities, learn by accessing the e-learning portal through teachers’ instruction and guidance. Even though, without better understanding of their need, expectation and the problem they encounter while using the e-learning system, sometimes difficult to make their learning become more effective. Understanding the antecedents of effectiveness in e-learning platform is very essential to create an appropriate e-learning environment. There are many factors which influence the effectiveness of e-learning such as use of e-learning system, users satisfaction, perceived usefulness, ease of use, system quality, contents delivery method, contents quality and self-efficacy could play important role in making the e-learning to be effective.